2012
DOI: 10.1080/10508422.2012.672907
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Academic Judgments and Behaviors: Applying a Multidimensional Ethics Scale to Measure the Ethical Academic Behavior of Graduate Students

Abstract: Using Reidenbach and Robin's Multidimensional Ethics Scale, this study investigated the relationships between background variables and students' ethical evaluations, judgments, and behavioral intentions using 3 scenarios involving dilemmas related to academic dishonesty. The sample included 436 master's students and 142 doctoral students. The study found that the participants used a combination of ethical philosophies to make ethical decisions. The respondents judged improper citations more harshly than acts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…This argument receives partial support from Taiwan-based studies conducted by Sun (2009) andYang (2012b). Most of the Taiwanese graduate students conduct thesis or dissertation using their native language (Chinese).…”
Section: Higher Education Students' Rcr-related Knowledgementioning
confidence: 99%
See 4 more Smart Citations
“…This argument receives partial support from Taiwan-based studies conducted by Sun (2009) andYang (2012b). Most of the Taiwanese graduate students conduct thesis or dissertation using their native language (Chinese).…”
Section: Higher Education Students' Rcr-related Knowledgementioning
confidence: 99%
“…Sun's research called an attention that appropriate paraphrasing-skills training should be included in English as a foreign language writing instruction so that students will effectively apply these strategies and avoid potential plagiarism (Sun, 2009). In another study, Yang (2012b) used three dimensions (plagiarism, authorship fraud, and falsification) to explore Taiwanese graduate students' understanding of research misconduct. The particular results showed that the students did not realize the seriousness of data fabrication or falsification.…”
Section: Higher Education Students' Rcr-related Knowledgementioning
confidence: 99%
See 3 more Smart Citations